Transient Response Harmonic Imaging: An Ultrasound Technique Related to Brain Perfusion - Postert, Thomas; Muhs, Andrea; Meves, Saskia; Federlein, Jens; Przuntek, Horst; Büttner, Thomas (Stroke (1970), 1998)
Background and Purpose —Gray-scale harmonic imaging is the first method to visualize blood perfusion and capillary blood flow with ultrasound after intravenous contrast agent application. The purpose of the present study was to evaluate the potential of transient response second harmonic imaging (TRsHI) to assess normal echo contrast characteristics in different brain areas by transcranial ultrasound. Methods —In 18 patients without cerebrovascular diseases, TRsHI examinations were performed bilaterally with the use of the transtemporal approach after application of 6.5 mL of a galactose-based microbubble suspension (400 mg/mL). The transmission rate was once every 4 cardiac cycles. Regional cerebral contrast was visually assessed and then quantified off-line with the use of time-intensity curves. In 4 different regions of interest (ROI) (posterior part of the thalamus [ROIa], anterior part of the thalamus [ROIb], lentiform nucleus [ROIc], and white matter [ROId]), the following parameters were evaluated: peak intensity, area under the curve (AUC), and time to peak intensity. AUC ratios for ROIc/a, d/a, c/b, and d/b were calculated. Results —In all patients parenchymal contrast enhancement was visually detectable. One hundred thirty-one characteristic time-intensity curves (baseline phase, peak contrast intensity, slow washout phase) were demonstrable in 144 ROIs. In ROIc and ROId, characteristic contrast curves could be observed most frequently (68/72 examinations), whereas time-intensity curves in ROIa and ROIb could not be evaluated because of inadequate contrast enhancement in 9 of 72 examinations. Time to peak intensity varied between 20 and 52 cardiac cycles; in 1 patient it was 88 cardiac cycles. In all individuals AUCs and in 16 of 18 subjects peak intensity in ROIc and ROId showed a 2- to 10-fold increase compared with ROIa and ROIb. In no examination did AUC ratios show a >2-fold side difference irrespective of the ROI. Conclusions —The present study demonstrates for the first time that TRsHI produces accurate contrast in different brain areas and represents an ultrasonic tool related to brain perfusion. Absolute values of quantitative parameters show high variations caused by different temporal bone thicknesses and a complex relationship between echo contrast concentrations and measurements of optic intensities. Ratios between different ROIs help to compare contrast enhancement in different brain areas. Furthermore, because of the fact that attenuation of contrast enhancement in TRsHI depends strictly on the insonation depth, harmonic imaging studies of brain perfusion cannot be compared directly with other imaging techniques such as positron emission tomography.